Expanding the morphologic spectrum of chromophobe renal cell carcinoma: A study of 8 cases with papillary architecture - Michalova, Kvetoslava; Tretiakova, Maria; Pivovarcikova, Kristyna; Alaghehbandan, Reza; Perez Montiel, Delia; Ulamec, Monika; Osunkoya, Adeboye; Trpkov, Kiril; Yuan, Gao; Grossmann, Petr; Sperga, Maris; Ferak, Ivan; et al. (Annals of diagnostic pathology, 2020)
Although typically arranged in solid alveolar fashion, chromophobe renal cell carcinoma (RCC) may also show several other architectural growth patterns. We include in this series 8 chromophobe RCC cases with prominent papillary growth, a pattern very rarely reported or only mentioned as a feature of chromophobe RCC, which is lacking wider recognition The differential diagnosis of such cases significantly varies from the typical chromophobe RCC with its usual morphology, particularly its distinction from papillary RCC and other relevant and clinically important entities. Of 972 chromophobe RCCs in our files, we identified 8 chromophobe RCCs with papillary growth. We performed immunohistochemistry and array Comparative Genomic Hybridisation (aCGH) to investigate for possible chromosomal aberrations. Patients were 3 males and 5 females with age ranging from 30 to 84 years (mean 57.5, median 60 years). Tumor size was variable and ranged from 2 to 14 cm (mean 7.5, median 6.6 cm). Follow-up was available for 7 of 8 patients, ranging from 1 to 61 months (mean 20.1, median 12 months). Six patients were alive with no signs of aggressive behavior, and one died of the disease. Histologically, all cases were composed of dual cell population consisting of variable proportions of leaf-like cells with pale cytoplasm and eosinophilic cells. The extent of papillary component ranged from 15 to 100% of the tumor volume (mean 51%, median 50%). Sarcomatoid differentiation was identified only in the case with fatal outcome. Immunohistochemically, all tumors were positive for CK7, CD117 and Hale's Colloidal Iron. PAX8 was positive in 5 of 8 cases, TFE3 was focally positive 3 of 8 tumors, and Cathepsin K was focally positive in 2 of 8 tumors. All cases were negative for vimentin, AMACR and HMB45. Fumarate hydratase staining was retained in all tested cases. The proliferative activity was low (up to 1% in 7, up to 5% in one case). Three cases were successfully analyzed by aCGH and all showed a variable copy number variation profile with multiple chromosomal gains and losses. CONCLUSIONS: Chromophobe RCC demonstrating papillary architecture is an exceptionally rare carcinoma. The diagnosis can be challenging, although the cytologic features are consistent with the classic chromophobe RCC. Given the prognostic and therapeutic implications of accurately diagnosis other RCCs with papillary architecture (i.e., Xp11.2 translocation RCC, FH-deficient RCC), it is crucial to differentiate these cases from chromophobe RCC with papillary architecture. Based on this limited series, the presence of papillary architecture does not appear to have negative prognostic impact. However, its wider recognition may allow in depth studies on additional examples of this rare morphologic variant.
Keywords: dospělí; nádory ledvin; nádorové biomarkery; DNA Copy Number Variations; Prognosis; Comparative Genomic Hybridization; senioři nad 80 let; Biomarkers, Tumor; Humans; srovnávací genomová hybridizace; diferenciální diagnóza; Carcinoma, Renal Cell; lidé středního věku; Kidney Neoplasms; Middle Aged; Aged, 80 and over; Carcinoma, Papillary; karcinom z renálních buněk; imunohistochemie; prognóza; papilární karcinom; mužské pohlaví; Immunohistochemistry; Adult; Chromosome Aberrations; Diagnosis, Differential; ženské pohlaví; lidé; Aged; senioři; Male; variabilita počtu kopií segmentů DNA; chromozomální aberace; Female